TOTAL PLATE COUNT OF BACTERIA AND pH IN MALE BALI CATTLE RUMEN FLUID SLAUGHTERED AT PESANGGARAN ABBATOIR - Mirahsanti, Ni Putu Nicky; Suarjana, I Gusti Ketut; Besung, I Nengah Kerta (Buletin Veteriner Udayana, 2022)
The purpose of this study was determined pH and the total plate count (TPC) of bacteria in the rumen of bali cattle. The research material is rumen fluid of male’s bali cattle as many as 17 samples. This research is observational analytic Cross Sectional approach with observations on TPC of bacteria and pH in the rumen. The data obtained are then presented descriptively. Then, the difference in the amount of TPC at a certain pH was analyzed by Independent Sample T- test . The results showed that the rumen pH range of bali cattle was 6.8 to 7 with the average was 6,4 ± 0,1 and the range of TPC numbers was 32 x 10 3 to 171 x 10 3 CFU /ml with the average was 74 x 10 3 ± 47 x 10 3 CFU/ml. There is no significant difference between the TPC at pH 6.8 and the TPC at pH 7.